DEMOGRAPHIC DIAGNOSIS OF LODZ REGION IN 2005-2012 - Olszewski, Witold Daniel (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
According to the diagnosis of the socio-economic situation shown in an update of “Lodz Regional Development Strategy 2020”, Lodz Province is subjected to the strongest depopulation processes in the country. The purpose of this article is spatial-temporal analysis of the demographic structure of the Lodz region using geographic information systems tools and spatial exploratory data analysis. The study mainly focuses on the characteristics of the variables that have the highest influence on the deepening problem of depopulation, i.e.: the number of births, the number of people in retirement age and the level of emigration. The research was performed on the basis of statistical data of the counties, in the period 2005-2012.